PRODUCT DEVELOPMENT OF PAKAN SINAYAN TOURISM VILLAGE, AGAM DISTRICT, WEST SUMATRA - Mozami Hasby; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the Product Development of Pakan Sinayan Tourism Village, Agam District, West Sumatra Province. Nature, Culture and Creative Works. This study uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurs by collecting data and information in the field. The key informants in this study were the Head of Service, Village Head, Tourists and the Community. In this study, the data collection techniques used were interviews, observation and documentation. Based on the results of the study, it can be concluded that the natural conditions are still maintained, the geographical climate is very cool, and is located at the foot of Mount Singgalang. The people there still maintain the authenticity of nature, customs and culture and also the people still maintain cultural values. Many tourists come to enjoy Atrakri in the village of Pakan Sinayan, the people there produce products from UMKM and also songket woven products with expensive handicrafts that can be exhibited and sold at national and international levels. Keywords: Development. Product. Tourism Village. Sinayan feed village